Agreement On Proto-Bantu Relative Verb Forms - Van de Velde, Mark1 (My University, 2022)
This chapter argues that Meeussen’s (1967) reconstruction of a Direct and an Indirect relative clause construction in Proto-Bantu (PB) is untenable, because there exists no scenario of morphosyntactic change that can lead from that reconstructed state of affairs to the relative clause constructions attested in contemporary Bantu. Although typologically unusual and widely attested across Bantu, relative verb forms that agree with the relativised noun phrase are not reflexes of a proto-construction with the same properties, but are the result of recent, parallel evolutions driven by a mechanism called the Bantu Relative Agreement (BRA) cycle. The only logically possible starting point from which the currently attested typological variation in Bantu relative clause constructions could have evolved is one in which relative verbs agreed with their subject. This conclusion has consequences for the reconstruction of the PB verbal template, which must have lacked a Pre-initial position.
Keywords: Proto-Bantu; Verb Forms; Relative